RECOGNITION CRITERIA OF BIOLOGICAL ASSETS IN AGRICULTURAL ACCOUNTING AND ITS CLASSIFICATION (Marketing Journal, 2025)
The article examines the recognition criteria of biological assets and their classification. The approaches and opinions of economists and experts on issues of recognition and classification of biological assets are studied, conclusions and proposals are d eveloped.
Keywords: agriculture; biological asset; recognition criteria; classification; international financial reporting standard